System center configuration manager 2007 unleashed - Meyler, Kerrie (Sams Pub., 2009)
This book is your most complete source for in-depth information about Microsoft System Center Configuration Manager 2007! System Center Configuration Manager 2007 Unleashed is a comprehensive guide to System Center Configuration Manager (ConfigMgr) 2007. ConfigMgr 2007 helps you manage servers and desktops, integrates SMS 2003 'feature pack' functionality, and adds new capabilities. It enables you to assess, deploy, and update servers, clients, and devices across physical, virtual, distributed, and mobile environments, including clients that connect only over the Internet. This book guides you through designing, deploying, and configuring ConfigMgr 2007 with detailed information on topics such as capacity planning, security, site design and hierarchy planning, server placement, discovery, native mode, and using Windows Server 2008. You will learn how to tackle challenges such as setting up DCM and OSD, customizing inventory, creating queries and using query results, and configuring asset intelligence. Detailed information on how to: Understand how ConfigMgr works; Plan your ConfigMgr deployment; Manage Windows Management Instrumentation (WMI); Architect for performance; Install or migrate to ConfigMgr 2007 with Windows 2003 or Windows 2008; Discover and manage clients; Create and distribute packages; Understand patch and compliance management; Create queries; Use reports; Deploy operating systems; Secure ConfigMgr 2007; Perform site maintenance; Back up ConfigMgr components.
Includes bibliographical references and index. - Print version record
Keywords: Microsoft System center configuration manager -- Computer programs; Computer networks -- Management -- Computer programs; Software configuration management -- Computer programs; Microsoft System center configuration manager / Computer programs; Microsoft system center configuration manager; Réseaux d'ordinateurs; Gestion; Logiciels; Logiciels; Gestion de configurations; Logiciels; Computer networks; Management; Computer programs; Software configuration management; Computer programs; Computer programs